2009
DOI: 10.1039/b901302d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient organic solar cells based on a poly(2,7-carbazole) derivative

Abstract: We have studied the utilization of PCDTBT, an alternating poly(2,7-carbazole) derivative, in organic bulk heterojunction solar cells. The effect of polymer molecular weight, PCDTBT:[60]PCBM ratio, and active layer thickness on the device performance is reported. The best performance was obtained when the number-average molecular weights (M n ) are around 20 kDa with a polydispersity index around 2.2. Both PCDTBT:[60]PCBM ratio and active layer thickness affect the light absorption and the charge transport prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
139
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 38 publications
9
139
0
Order By: Relevance
“…It is thus not surprising that typically BHJ OPVs with a polymer/PC 70 BM active layer show improved performance than the OPVs with polymer/PC 60 BM active layers. 7,17,18 By controlling the BTT-DPP/PC 70 BM composition ratio we were able to optimise the device power conversion efficiencies to a maximum of 3.1%. In addition, we have shown that device J SC is limited by the efficiency of the PC 70 BM exciton dissociation, attributed to the tendency of PCBM to form large, relatively pure domains with domain sizes longer than the PCBM exciton diffusion length.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus not surprising that typically BHJ OPVs with a polymer/PC 70 BM active layer show improved performance than the OPVs with polymer/PC 60 BM active layers. 7,17,18 By controlling the BTT-DPP/PC 70 BM composition ratio we were able to optimise the device power conversion efficiencies to a maximum of 3.1%. In addition, we have shown that device J SC is limited by the efficiency of the PC 70 BM exciton dissociation, attributed to the tendency of PCBM to form large, relatively pure domains with domain sizes longer than the PCBM exciton diffusion length.…”
mentioning
confidence: 99%
“…7 Low bandgap BHJ devices utilizing PC 70 BM as an electron acceptor have consistently performed better than the devices with the more common electron acceptor PC 60 BM. 7,[17][18] Although these two fullerene derivatives have similar ionisation potential (IP), electron affinity (EA) and sizes, the increase in device efficiencies when PC 70 BM is used has been attributed to its improved light absorption. 7,19 The increased light absorption of PC 70 BM relative to PC 60 BM has been attributed to its lower symmetry resulting in otherwise forbidden singlet transitions in PC 60 BM becoming allowed.…”
mentioning
confidence: 99%
“…The performance metrics including relevant statistics are summarized in Table 1. It has previously been demonstrated that the Fill Factor (FF) and PCE fall off rapidly for junctions > 80 nm for PCDTBT:PC70BM [133], and we also observe the same trend. This has been attributed to poor charge transport in this blend, in particular low hole mobilities which leads to significant bimolecular recombination under 1 sun operating conditions.…”
Section: Photovoltaic Performance Of Solar Cellssupporting
confidence: 68%
“…The structures of the two different polymers are provided Figure 1. These systems have been extensively studied [54,104,107,132,133] and are known to have quite different charge transport properties (PTB7:PC70BM being superior). In this work we varied the junction thickness as an experimental parameter so as to access a range of key charge transport properties (recombination and mobility) in a systematic manner and study their impact upon device performance.…”
Section: Photovoltaic Performance Of Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation